1982
DOI: 10.14430/arctic2325
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Skeletal Disturbances of North American Prey Carcasses

Abstract: More than 125 carcasses and skeletal remains of wild bison, moose, and whitetail deer were examined in the field. Most were from closely documented episodes of predation, mass drownings, or other natural causes of death. Predictable and unusual kinds of bone and carcass utilization by timber wolves and bears are described. The variables emphasized include sectioningof carcasses by feeding predators, distribution and dispersal of bones at kill sites, gnaw damage to bones in homesites, kill sites and scavenge si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
0
13

Year Published

1989
1989
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(162 citation statements)
references
References 14 publications
6
143
0
13
Order By: Relevance
“…scavengers. Other possible explanations for the limited evidence of carnivore gnawing are a predominance of winter kills and/or high prey abundance (Haynes, 1982(Haynes, , 1983; however, these alternatives seem unlikely because in the region today caribou carcasses are converted into broad scatters of gnawed and shattered bones within several years of death. Some of these bones may persist for decades on the ground surface, but they persist as gnawed fragments, and this is not the condition of the majority of Pleistocene bones we find.…”
Section: Taphonomic Pathwaysmentioning
confidence: 99%
“…scavengers. Other possible explanations for the limited evidence of carnivore gnawing are a predominance of winter kills and/or high prey abundance (Haynes, 1982(Haynes, , 1983; however, these alternatives seem unlikely because in the region today caribou carcasses are converted into broad scatters of gnawed and shattered bones within several years of death. Some of these bones may persist for decades on the ground surface, but they persist as gnawed fragments, and this is not the condition of the majority of Pleistocene bones we find.…”
Section: Taphonomic Pathwaysmentioning
confidence: 99%
“…showing that the animal died at some time after the beginning of September and at the latest before April or May (Legge and Rowley-Conwy 1988,31), at all events within the colder half of the year. The majority of bones show signs of carnivore gnawing and the skeleton may most plausibly be interpreted as the remains of a winter wolf kill (Haynes 1982). It is not suggested that man is in any way connected with the death of the elk.…”
Section: Miesenheim I1mentioning
confidence: 99%
“…Bones and hide are believed to be a very important component of the Wolverine's winter economy (Banci 1994;Haynes 1982). Cache-sites appear to be closely frequented until the nutritive value is exhausted, judging from the well-used system of trails and tracks of varying ages in the vicinity of such sites.…”
Section: Resultsmentioning
confidence: 99%